Feel Fabulous Forever : The Anti-Ageing Health and Beauty Bible - Fairley, Josephine and Stacey, Sarah (London Kyle Cathie Ltd., 1999)
Catering for a wide range of lifestyles and budgets, this is a guide for mature women seeking advice on anti-ageing strategies and techniques, including hundreds of creams and other products. The book covers make-up, massage, HRT, supplements, skin and hair care, and "anti-gravity" techniques.
Include Index and Illustration
Keywords: Women--Health and hygiene -- Aging--Prevention -- Beauty, Personal